2013
DOI: 10.1039/c2ee23716d
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of smooth and aligned single walled carbon nanotube/silicon hybrid solar cells

Abstract: Smooth and aligned single walled carbon nanotube (SWNT) thin films with improved optoelectronic performance are fabricated using a superacid slide casting method. Deposition of as made SWNT thin film on silicon (Si) together with post treatments result in SWNT/Si hybrid solar cells with unprecedented high fill factor of 73.8%, low ideality factor of 1.08 as well as overall dry cell power conversion efficiency of 11.5%. Broader contextThe unique optical, electrical and mechanical properties as well as solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 48 publications
5
111
0
Order By: Relevance
“…21 We have carried out further experiments on different film thicknesses. Solar cells with two relatively thick CNT films (with decreased optical transparencies of 84.8% and 74.7%, respectively) have been made and tested (Fig.…”
Section: N(cnt-g-si)mentioning
confidence: 99%
“…21 We have carried out further experiments on different film thicknesses. Solar cells with two relatively thick CNT films (with decreased optical transparencies of 84.8% and 74.7%, respectively) have been made and tested (Fig.…”
Section: N(cnt-g-si)mentioning
confidence: 99%
“…An important factor in many devices is the degree of coverage of the films on the silicon surface, itself dependent on the films’ porosity. Jung et al [17], Li et al [28] and Tune et al [42] have shown that alignment of the nanotubes by solution shearing (as known as slide casting, liquid film shearing, shear force casting) from solutions of either the nanotubes dissolved natively in chlorosulphonic acid (Jung, Li), or the nanotubes dissolved as polyelectrolyte salts in polar, aprotic solvent (Tune) yields higher performing devices than their randomly oriented counterparts, and explained these observations with reference to the better surface coverage provided by such films.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is more behind this because it did not occur in our previous report where a reduced V OC was observed and was assigned to the possible short circuits caused by the AuNPs bridging the Si with the front metal electrode. [24,55] As the doping is performed in a different manner here, the possibility of bridging by AuNPs is probably reduced dramatically owing to the elimination of the contact between the AuCl 3 stock solution and the Si surface during the doping. As the short circuits normally cause a change in the heterojunction diode properties and there is no significant change in ideality, J sat , and F B for GOCNT/Si devices with AuCl 3 -doped electrodes (there even seems to be a slight improvement in these parameters; Fig.…”
Section: Aucl 3 Bath Dopingmentioning
confidence: 99%